Contention Window and Residual Battery Aware Multipath Routing Schemes in Mobile Ad-hoc Networks - Tilwari, Valmik; Hindia, Mhd Nour; Dimyati, Kaharudin; Qamar, Faizan; Abu Talip, Mohamad Sofian (Faculty of Engineering, Universitas Indonesia, 2019)
In mobile ad hoc networks, limited energy resources and traffic congestion at the nodes are crucial issues due to the nodes being battery operated and flooding the network with packets, respectively. These issues degrade network routing performance in terms of quality of service. In this study, we proposed a contention window and residual battery-aware multipath routing scheme to enhance network performance. Our proposed routing scheme has successfully diverted the traffic load from a low energy node to a high energy node while also controlling congestion among intermediate nodes. A multi-criteria decision-making technique was also used for the selection criteria of an intermediate node in the optimal path, based on the mobility and window size contention of nodes. Eventually, the contention window and residual battery-aware multipath routing scheme has enhanced throughput, attenuated the packet loss ratio, and reduced the energy consumption in comparison to a conventional multipath optimized link state routing protocol routing scheme. © IJTech 2019.